PERCEIVED BARRIERS TO CAREER PROGRESSION IN THE WESTERN AUSTRALIAN STATE PUBLIC SECTOR - Cullen, Lisa; Christopher, Theo (The journal of contemporary issues in business and government, 2007)
The present study fills a gap in prior research by examining perceived career barriers of both male and female accountants working in the Western Australian state public sector. A sample of qualified accountants were sent questionnaires requesting them to indicate the level of importance of 24 listed career-related barriers with the option of adding additional barriers. Two additional barriers were added from the responses. Findings observed a number of career-related barriers. The importance of these barriers was found to be related to demographic variables. Correlation analysis found that gender, age, years of experience and years working in the public service were all significantly related of the extent of work-life balance barriers. Age was found to be significantly related to the total of all barriers and individual barriers. Qualifications were also found to be related to external and individual barriers. The implications of the findings are that barriers are present and measures need to be undertaken to remove these barriers.